New approaches for long-term conservation of rooster spermatozoa - Janosikova, Martina; Petricakova, Kristyna; Ptacek, Martin; Savvulidi, Filipp Georgijevic; Rychtarova, Jana; Fulka, Josef (Poultry science, 2023)
In contrast to the livestock industry, sperm cryopreservation has not yet been successfully established in the poultry industry. This is because poultry sperm cells have a unique shape and membrane fluidity, differing from those of livestock sperm. The objective of this review is to discuss the cellular and molecular characteristics of rooster spermatozoa as a cause for their generally low freezability. Furthermore, here, we discuss novel developments in the field of semen extenders, cryoprotectants, and freezing processes, all with the purpose of increasing the potential of rooster sperm cryopreservation. Currently, it is very important to improve cryopreservation of rooster sperm on a global scale for the protection of gene resources due to the incidence of epidemics such as avian influenza.
Keywords: uchování spermatu; Cryopreservation; kur domácí; Semen Preservation; Chickens; Semen; sperma; Poultry; poultry; Spermatozoa; oxidative stress; Sperm Motility; cryoprotectants; kryoprezervace; zmrazování; motilita spermií; kryoprotektivní látky; mužské pohlaví; spermie; Cryoprotective Agents; zvířata; cryopreservation; Freezing; Animals; Male; drůbež